The quality of vermicompost from various sources composted with earthworm Perionyx excavates. Issue 1 (1st March 2022) - Riwandi,; Muktamar, Zainal; Hasanudin,; Anandyawati,; Allsari, Vira
Abstract: The quality of vermicompost depends on the source of earthworms feed such as animal waste (cows, buffaloes, chickens, and goats). The aim of the study was to obtain high quality vermicompost and to determine the parameters of vermicompost in accordance with the compost quality standard from SNI 19-7030-2004. The experimental design was Completely Randomized Design (CRD) with the treatment of types animal manures: consisted of cow, buffalo, chicken, and goat manures with 6 replications, so there were 24 experimental units. The results showed that the 9 parameters of vermicompost tested complied to the quality criteria of compost from SNI 19-7030-2004. The significant finding of this study was the weight of the remaining earthworms decreased from 12 g at initial weight to 2.42 g for cow dung, 2.38 g for buffalo dung, 1.62 g for chicken manure and 0, 63 g for goat dung after harvesting the vermicompost. The highest quality of vermicompost according to the criteria of SNI 19-7030-2004 was cow dung, followed by buffalo dung, goat dung, and chicken manure. According statistical analysis showed that pH (H2 O, 1:5 w/v) is 8.90 (highest) for chicken manure, 8.60 (medium) for cow dung as well as 8.46 (medium) for goat dung, and 7.90 (low) for buffalo dung. Water content are not significant for all sources of vermicompost which is 50% more. Temperatures of vermicompost from goat dung (28.70°C) and chicken manure (28.29°C) are significant significantly higher than cow dung (27.68°C), and buffalo dung (27.89°C). Organic C content, total N content, and C/N ratio of vermicompost used descriptive analysis. Organic C content was highest in vermicompost derived from buffalo dung, followed by cow dung, chicken manure, and goat dung as well as total N content from goat dung, chicken manure, buffalo dung, and cow dung. Also C/N ratio from low to high are goat dung, chicken manure, cow dung, and buffalo dung.